Design, synthesis and application of a library of novel bioactive surfactants as a tool for the production of functionalised microparticles - Cuzzucoli Crucitti, Valentina (2021)
The development of novel biomaterials needs to move towards a rational design from both a research and commercial point of view. In this context, the rise of combinatorial chemistry approaches and analytical high-throughput methods have been a breakthrough in the design and screening of new materials. In the polymer chemistry field, these methods led to the synthesis of libraries of novel polymers with significant savings in time, materials waste, and labour. Additionally, in the biomaterials screening process, it is important to find new biological alternative tests in order to have a deeper understanding on the interaction of the biomaterials with their immediate extracellular environment and, consequently, derive more realistic biological models/assays that mimic real human conditions. In the work presented here, it was reported the synthesis of novel amphiphilic copolymers presenting target chemistry and biological properties. For the first time, this polymeric amphiphiles were used in a flow-focusing microfluidic apparatus where they acted as surfactants for the production of a library of monodisperse microparticles with bio-instructive surface, to be used as potential 3D platform for controlling surface-cell response. In Chapter 3, a library of new polymeric surfactant materials was designed and synthesised by using a high-throughput synthesiser. In addition, in this chapter, the combination of a novel high-throughput analytical technique and the use of a machine learning analysis delivered ‘on-demand’ product property assessment. Chapter 4 outlines how the use of designed polymeric surfactants and droplet microfluidics can exert control over both the surface chemistry and size distribution of microparticle materials, demonstrating their critical importance for controlling surface-cell response. In Chapter 5 the main aim was to develop and synthesise cationic random and block amphiphilic copolymers, by using two different radical polymerisation techniques. Also, the ability to self-assemble in water and to act as surfactant were investigated using the droplets microfluidics setup previously discussed.